143 Olanzapine for the prevention and treatment of cancer-related nausea and vomiting in adults: a new cochrane systematic review. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Sutherland, A; Naessens, K; Plugge, E; Ware, L; Head, K; Burton, MJ; Wee, B
Abstract : Background: The use of olanzapine as an anti-emetic represents a new use of an old second generation atypical anti-psychotic drug. Objectives: To assess the efficacy and safety of olanzapine when used as an anti-emetic in the prevention and treatment of nausea and vomiting related to cancer in adults. Results: We included 14 RCTs (1917 participants). Eight studies await classification and 13 are ongoing. Olanzapine probably doubles the likelihood of freedom from nausea and vomiting during chemotherapy from 25% to 50% (RR 1.98, 95% CI 1.59 to 2.47; 561 participants; solid tumours; HEC or MEC therapy; moderate quality evidence) when added to standard therapy. Number Needed to Treat for additional benefit (NNTB) was 5 (95% CI 3.3 to 6.6). It is uncertain if olanzapine increases the risk of serious adverse events (absolute risk difference 0.7% more, 95% CI 0.2 fewer to 5.2 more, RR 2.46, 95% CI 0.48 to 12.55; low quality evidence). Olanzapine may increase other adverse events (RR 1.71, 95% CI 0.99 to 2.96; Iow quality evidence) and probably increases somnolence and fatigue compared to no treatment or placebo (anticipated absolute risk 8.2% more, 95% CI 1.9 to 18.8; participants=464; studies=5; moderate quality evidence). Olanzapine probably reduces delayed and vomiting. It is unclear if efficacy differs between 5 mg and 10 mg doses. We cannot exclude the possibility that 5 mg may be associated with a lower risk of somnolence and fatigue than 10 mg. Conclusions: There is moderate quality evidence that oral olanzapine increases freedom from nausea and vomiting in adults undergoing chemotherapy for solid tumours. There is uncertainty whether it increases serious adverse events. It may increase the likelihood of other adverse events and probably increases somnolence and fatigue. There is uncertainty about the relative benefits and harms of lower (5 mg) and higher (10 mg) doses.